Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I've been struggling with figuring out how to add powers of $i$.

For example, the result of $i^3 + i^4 + i^5$ is $1$. But how do I get the result of $i^3 + i^4 + ... + i^{50}$? Writing it all down would be pretty mundane...

It has to do something with division by 4, since the "power cycle" of $i$ repeats every fourth power.

Thank you for any clues.

share|improve this question
    
You need to wrap the 50 in curly braces. –  Rahul Sep 5 '10 at 13:45
    
Is there a typo in $i^3+i^4+\dots +i^50$? Do you mean $i^3+i^4+\dots +i^{50}$? –  Américo Tavares Sep 5 '10 at 13:47
1  
Yes, sorry for the typo. –  jkottnauer Sep 5 '10 at 13:52
add comment

4 Answers

up vote 11 down vote accepted

From $i^2=-1$ you get $i^{4n}=1$, $\quad i^{4n+1}=i$, $\quad i^{4n+2}=-1$ and $i^{4n+3}=-i$.

Then you just count your positive and negative multiples of $1$ and $i$.

In particular, $i^3+i^4+\cdots+i^{50}=0$.

share|improve this answer
add comment

Observing that $i^{3}+i^{4}+\ldots +i^{50}$ is a geometric progression with ratio $i$, first term $i^3$ and $50-3+1=48$ terms, we have

$i^{3}+i^{4}+\ldots +i^{50}=i^{3}\times \dfrac{1-i^{50-3+1}}{1-i}=i^{3}\times \dfrac{1-i^{48}}{1-i}=i^{2}i\times \dfrac{1-(i^{2})^{24}}{1-i}$

$=-i\dfrac{1-(-1)^{24}}{1-i}=-i\dfrac{1-1}{1-i}=0$

Edit: "arithmetic" corrected to "geometric"

share|improve this answer
    
Tavares: Its not an arithmetic progression but a geometric progression. –  anonymous Sep 5 '10 at 13:57
    
@Chandru1: Of course! Thanks! Corrected. –  Américo Tavares Sep 5 '10 at 14:10
    
+1 for generality. –  J. M. Sep 5 '10 at 14:12
    
+1 for simplicity. –  Quixotic Oct 4 '10 at 19:35
add comment

HINT $\rm\quad\quad i^3 + \: i^4 \; + \:\;\cdots\;\: + \; i^k = 0\ \:\iff\: k\:\equiv\: 2 \:\pmod 4$

Generally, suppose that $\rm\: z \:$ has order $\rm m>1\:.$ Therefore $\rm\; z^n = 1 \iff\ m\:|n\;\;\:$ hence:

LEMMA $\quad\rm z^j + z^{j+1} + \:\cdots + z^k = 0\;\; \iff \rm\: k \:\equiv\;\; j \:-\: 1 \:\pmod m $

Proof: $\;\;\;\;\rm \displaystyle z^j \ (1+z+\cdots + z^{k-j}) \;=\; z^j \: \frac{1-z^{k-j+1}}{1-z} = 0 \;\iff\; \rm m\:|\:k-j+1\quad\;$

share|improve this answer
    
This is pretty opaque to a lowly peon such as myself! –  The Chaz 2.0 Jul 16 '13 at 0:00
add comment

We have $$i^{3} + i^{4} + i^{5} = 1 = i^{3} + i^{4} + i^{5} + i^{6} + i^{7} + i^{8} + i^{9} = i^{3} + i^{4} + \cdots +i^{4n+1}$$

Now $i^{50}=1 \times -1$, therefore we have the sum is $0$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.